A Method Of Lines Approach In The Numerical Solution Of 1-Dimensional Schrodinger's Equation - Lawal Sa’adu; M. A. Hashim; Karsono A. Dasuki; Bahrom Sanugi (Canadian Center of Science and Education, 2024)
Non-Indexed Publication